On certain spectral features inherent to scalar type spectral operators - Markin, M. V. (Methods of Functional Analysis and Topology, 2017)
Important spectral features such as the emptiness of the residual spectrum, countability of the point spectrum, provided the space is separable, and a characterization of spectral gap at 0, known to hold for bounded scalar type spectral operators, are shown to naturally transfer to the unbounded case.